Bowenoid papulosis of genitalia responding to topical 5-Fluorouracil - Ragunatha Shivanna; Meenakshi Kapoor; B Niranjana Murthy; Gangaiah Narendra (Wolters Kluwer Medknow Publications, 2018)
Bowenoid papulosis (BP), a rare disease with malignant potential, is a distinct clinicopathological entity strongly associated with human papillomavirus (HPV) infection. We described an adult male presenting with well defined, purplish papules of varying size with verrucous to smooth surface distributed discretely over medial side of the left thigh, scrotum, and penile shaft. Histopathology showed focal areas of full thickness epidermal atypia comprising irregularly arranged nuclei which are large, hyperchromatic, and crowded at few places. Pap smear from spouse showed inflammatory infiltrate with moderate-to-severe dysplasia. The patient was treated with topical 5-fluorouracil. Excellent response was noticed at the end of 2 weeks. A patient with BP should be thoroughly educated regarding HPV infection and emphasis should be on prevention. Female patients or sexual partners of male patient with BP are at the risk of developing cervical cancer and hence should be followed with regular cytologic, colposcopic, and histologic examinations.